Enhanced Context Sensitive Flash Codes. (9th January 2021) - Baruch, Gilad; Klein, Shmuel T; Shapira, Dana
Abstract: A major property of flash memory is that a 0-bit can be changed into a 1-bit, but the symmetric task of switching from a 1-bit to a zero may only be performed in blocks and is therefore often prohibited. This led to the development of rewriting codes using the same storage space more than once, subject to the constraint that 0-bits can be changed into 1-bits, but not vice versa. Context sensitive rewriting codes extend this idea by also incorporating information gathered from surrounding bits. Several new context sensitive rewriting codes are presented and analyzed, some of which are better than the state of the art for sparse input. Empirical simulations show a good match with the theoretical results.